Targeting macrophage Syk enhances responses to immune checkpoint blockade and radiotherapy in high-risk neuroblastoma - Rohila, Deepak; Park, In Hwan; Pham, Timothy V.; Jones, Riley; Tapia, Elisabette; Liu, Kevin X.; Tamayo, Pablo; Yu, Alice; Sharabi, Andrew B.; Joshi, Shweta (Frontiers in Immunology, 2023)
Background Neuroblastoma (NB) is considered an immunologically cold tumor and is usually less responsive to immune checkpoint blockade (ICB). Tumor-associated macrophages (TAMs) are highly infiltrated in NB tumors and promote immune escape and resistance to ICB. Hence therapeutic strategies targeting immunosuppressive TAMs can improve responses to ICB in NB. We recently discovered that spleen tyrosine kinase (Syk) reprograms TAMs toward an immunostimulatory phenotype and enhances T-cell responses in the lung adenocarcinoma model. Here we investigated if Syk is an immune-oncology target in NB and tested whether a novel immunotherapeutic approach utilizing Syk inhibitor together with radiation and ICB could provide a durable anti-tumor immune response in an MYCN amplified murine model of NB. Methods Myeloid Syk KO mice and syngeneic MYCN-amplified cell lines were used to elucidate the effect of myeloid Syk on the NB tumor microenvironment (TME). In addition, the effect of Syk inhibitor, R788, on anti-tumor immunity alone or in combination with anti-PDL1 mAb and radiation was also determined in murine NB models. The underlying mechanism of action of this novel therapeutic combination was also investigated. Results Herein, we report that Syk is a marker of NB-associated macrophages and plays a crucial role in promoting immunosuppression in the NB TME. We found that the blockade of Syk in NB-bearing mice markedly impairs tumor growth. This effect is facilitated by macrophages that become immunogenic in the absence of Syk, skewing the suppressive TME towards immunostimulation and activating anti-tumor immune responses. Moreover, combining FDA-approved Syk inhibitor, R788 (fostamatinib) along with anti-PDL1 mAb provides a synergistic effect leading to complete tumor regression and durable anti-tumor immunity in mice bearing small tumors (50 mm3) but not larger tumors (250 mm3). However, combining radiation to R788 and anti-PDL1 mAb prolongs the survival of mice bearing large NB9464 tumors. Conclusions Collectively, our findings demonstrate the central role of macrophage Syk in NB progression and demonstrate that Syk blockade can “reeducate” TAMs towards immunostimulatory phenotype, leading to enhanced T cell responses. These findings further support the clinical evaluation of fostamatinib alone or with radiation and ICB, as a novel therapeutic intervention in neuroblastoma.